Gamification and Experiential Learning in Education - Joshi, Saru (Bodhi: An Interdisciplinary Journal, 2024)
The term “gamification” refers to the practice of incorporating elements of game design into non-game contexts such as websites, online games, and learning management systems. Gamification’s end purpose is to get people involved so as to motivate them to share, collaborate, and talk to one another. The goal of gamifying material is to increase user participation, particularly when it comes to unpleasant learning, like completing a study on a topic either boring or unpleasant to learn. Game elements used in gamification include the goal of making learning more fun; gamification attempts to model the classroom environment after a first-person video game. The purpose is to improve education by stimulating interest amongst students. More specifically, “learning through reflection on doing” captures the essence of the experiential learning process. While students may be required to reflect on their work as part of a hands-on learning activity, this is not always the case. The suggested study addresses the merits and cons of gamification for experiential learning. This paper endeavors to make some conclusions, bringing into the limelight of education the incorporation of different cross-disciplinary dimensions in education by adding gamifying and understanding its core aspects in the process of teaching and learning. Gamification is added to a new approach to learning through various games using devices. This paper covers learning by doing, experiential learning, gamification, and their aids in the education system. The data were collected from the secondary sources (literature, books, Google, etc.). To conclude, it is stated that the rigid curriculum and formal learning are replaced by cross functional content that can satisfy curiosity, and thus, informal learning can occur. The new tools and approach to making its titles in social communication have brought an era where we have to rethink learning, knowledge sharing, and collaborative learning by understanding the new concept of gamifying and experiential learning.